(untitled) (Società e diritti, 2025)
The term post-Fordism refers to the transformations that have occurred within economic processes since the 1980s. Flexible accumulation, the orientation of production towards demand, the valorization of the communicative sphere. This contribution aims to analyze the transformation of institutional violence in the transition from post-Fordism to Fordism. In particular, if before violence was transparent and inclusive, today it is opaque and exclusive. With institutional violence, we refer in particular to the violence that is committed within places of detention, such as prisons, hotspots, police stations and CPRs. From the aspect of delocalization it becomes possible to define the peculiarity of post-Fordist violence. The exercise of violence lives a singular paradox: if outside calls for non-violence, projects focused on conflict prevention and peaceful coexistence proliferate, and violent images and scenes are removed from the media, within institutions this paradigm is reversed. Violence, removed from official society, is carried out in hidden places. As for externalization, violence in these places (as in the case of the Guantanamo prison) is carried out by personnel external to the police, therefore not subject to the ethical protocols that regulate the work of the forces responsible for working in the institutions.